Photographs of a group of officers who attended a training course run by J. J. O'Connell in Cork starting 22nd January 1916 - Irish Volunteers; O'Donoghue, Florence, 1895-1967; Bureau of Military History, 1913-1921 (1916)
Five copies of the photograph in various sizes with a typed note listing the officers on Bureau of Military History headed paper.
Keywords: O’Connell, J. J., -- 1888-1944; Ireland -- History -- 1910-1921; Ireland -- History -- 1922-